2007
DOI: 10.1088/0960-1317/17/7/021
|View full text |Cite
|
Sign up to set email alerts
|

Pressure drop of laminar gas flows in a microchannel containing various pillar matrices

Abstract: The pressure drop of gas flows in a microchannel filled with a dense pillar matrix was investigated with specific attention to a pillar shape. Pillars of height 250 µm and aspect ratio of about 10 were etched in silicon using an optimized Bosch deep reactive ion etching process. The pressure drop head-loss coefficient due to compression and expansion of gas at the inlet and outlet of the pillar matrix was estimated to be about 1.4 for an opening ratio of 10. A comparison of friction factor correlations for cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 15 publications
1
31
1
1
Order By: Relevance
“…Using water flow, they obtained a maximum heat transfer coefficient of around 55,000 W/m 2 C. John et al [35] compared the performance of square and circular pin fins and noted that the figure of merit, defined as the heat transfer performance to pressure drop penalty, was higher for circular pin fins at Re < 300, while reverse was true at higher Re. Vanapalli et al [36] studied additional fin shapes of ellipse and diamond in gas flow, but these have not been studied in liquid flows. Lee et al [37] studied their patented parallelogram cross-sectional fins with the side walls parallel to the flow and the oblique front and rear sides facing at an angle.…”
Section: Fins In Single-phase Liquid Flowmentioning
confidence: 99%
“…Using water flow, they obtained a maximum heat transfer coefficient of around 55,000 W/m 2 C. John et al [35] compared the performance of square and circular pin fins and noted that the figure of merit, defined as the heat transfer performance to pressure drop penalty, was higher for circular pin fins at Re < 300, while reverse was true at higher Re. Vanapalli et al [36] studied additional fin shapes of ellipse and diamond in gas flow, but these have not been studied in liquid flows. Lee et al [37] studied their patented parallelogram cross-sectional fins with the side walls parallel to the flow and the oblique front and rear sides facing at an angle.…”
Section: Fins In Single-phase Liquid Flowmentioning
confidence: 99%
“…Interestingly, it has been reported that the correlations used to predict the pressure drop for fluid flow across pin fin-tube bundles in conventional scale systems need to be modified for microscale counterparts [15]. These microscale hydrodynamic correlations have been developed in recent years for a variety of geometric fin configurations (aligned and staggered), fin types (tubular or non-tubular) and their aspect ratios (ratio of the height of a pin to its diameter) [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, employing the existing models may lead to significant inaccuracy in the analysis of flow through low aspect ratio cylinders embedded inside channels. The experimental results reported by Kosar et al [3], Vanapalli et al [14], and Yeom et al [15] revealed that in the case of low aspect ratio cylinders, these two-dimensional models failed. Therefore, a more general model should consider the channel walls' effects in the analysis in order to successfully predict the flow through the cylinder array.…”
Section: Introductionmentioning
confidence: 95%